Interleukin-17 Receptor D in Physiology, Inflammation and Cancer - Girondel, Charlotte; Meloche, Sylvain (Frontiers in Oncology, 2021)
Interleukin-17 receptor D (IL-17RD) is an evolutionarily conserved member of the IL-17 receptor family. Originally identified as a negative regulator of fibroblast growth factor (FGF) signaling under the name of Sef (Similar expression to FGF genes), IL-17RD was subsequently reported to regulate other receptor tyrosine kinase signaling pathways. In addition, recent studies have shown that IL-17RD also modulates IL-17 and Toll-like receptor (TLR) signaling. Combined genetic and cell biology studies have implicated IL-17RD in the control of cell proliferation and differentiation, cell survival, lineage specification, and inflammation. Accumulating evidence also suggest a role for IL-17RD in tumorigenesis. Expression of IL-17RD is down-regulated in various human cancers and recent work has shown that loss of IL-17RD promotes tumor formation in mice. However, the exact mechanisms underlying the tumor suppressor function of IL-17RD remain unclear and some studies have proposed that IL-17RD may exert pro-tumorigenic effects in certain contexts. Here, we provide an overview of the signaling functions of IL-17RD and review the evidence for its involvement in cancer.